Salinization effects on coastal ecosystems: a terrestrial model ecosystem approach. (21st January 2019) - Pereira, C. S.; Lopes, I.; Abrantes, I.; Sousa, J. P.; Chelinho, S.
Abstract : In coastal areas, intrusion/irrigation with seawater can threaten biodiversity along with crop yields, and the leaching of salts from areas affected by these processes can increase the salinity of water bodies nearby. The aims of this study were to evaluate the effects of salinization on coastal soil ecosystems due to saline intrusion/irrigation. Terrestrial model ecosystems were used to simulate two soil salinization scenarios: (i) seawater intrusion and irrigation with distilled water and (ii) seawater intrusion and irrigation with saline water. Three sampling periods were established: T0—after acclimation period; T1—salinization effects; and T2—populations' recovery. In each sampling period, the abundance of nematodes, enchytraeids, springtails, mites and earthworms, and plant biomass were measured. Immediate negative effects on enchytraeid abundance were detected, especially at the higher level of saltwater via intrusion+irrigation. Eight weeks after the cessation of saline irrigation, the abundance of enchytraeids fully recovered, and some delayed effects were observed in earthworm abundance and plant biomass, especially at the higher soil conductivity level. The observed low capacity of soil to retain salts suggests that, particularly at high soil conductivities, nearby freshwater bodies can also be endangered. Under saline conditions similar to the ones assayed, survival of some soil communities can be threatened, leading to the loss of biodiversity. This article is part of the theme issue 'Salt in freshwaters: causes, ecological consequences and future prospects'.